Mineral oil recovery from cork granules by a mechanical compression method: Compression cycles analysis - Paulo S. S. Porto (2017)
The aim of this study was to investigate the recovery of mineral oil from oil-loaded regranulated cork (RGC) particles by a mechanical compression method using a pneumatic press, as well as to evaluate their possible reuse in consecutive loading/compression cycles. The oil-impregnated RGC was inserted into a cylindrical compression barrel, and then compressed using a conical piston. The recovered oil percentage (%RO) was evaluated as function of the applied mechanical compression pressure (p = 0.2 -0.7 MPa), compression time (t(C) = 1, 3 and 5 min), waiting time between each compression (t(W) = 1 min or t(W) = t(C)), height of the compression barrel filled with RGC particles (H <= 12.4 cm)/mass of RGC particles saturated with oil (m(SO)) and number of compressions (1 < N-C < 3). Two configurations of the cylindrical barrel were used: a) only perforated at the bottom and b) perforated at the bottom and in the cylindrical surface. A higher oil recovery was achieved using the second configuration since oil flows in the axial and radial directions, decreasing the distance that oil has to travel to come out the barrel. The particles reusability was tested in ten cycles of saturation/compression using the optimized compression variables (p = 0.5 MPa, N-C = 3, t(C) = 3 min, t(W) = 1 min and H similar to 12.4 cm).